SOME STYLISTIC FEATURES OF CONTEMPORARY ENGLISH INTERNET MASS MEDIA TEXTS IN THE RELIGIOUS (ORTHODOX) DOMAIN - Krugl'akova, G.V; Chukarkova, O.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
It is hard to overestimate the degree of social importance of the Internet mass media at present. Nowadays the Internet media play a paramount role providing the public with up-to-date information. The cyberspace presents a totally different communication medium, in which the addressee is influenced by web-tests. Web-texts possess unique features due to the extralinguistics of the online mass media. This article represents a linguistic research of modern English web-texts on religious topics written by Orthodox priests who are native English language speakers. The authors of the article have analyzed the correlation between the specific features of religious texts and those of web-texts bearing in mind the fact that the studied religious material is publicized online. As a result, it has been discovered that the online medium produces a significant effect on the choice of the linguistic features of the texts. These texts are partially losing some of their conventional features, being transformed into a new type of text (a web-text). This transformation is based on the change of the stylistic register typical of conventional religious texts for a more colloquial one. Nevertheless, some lexical and syntactical features of the traditional religious discourse do not only remain present in online texts, but also become transformed to comply with the linguistic requirements of the cyberspace.